Nanofibrous Membrane Dressings Loaded With Sodium Hydrogen Sulfide/Endothelial Progenitor Cells Promote Wound Healing - Lian, Jie; Ju, Guanqun; Cai, Xueyao; Cai, Yuchen; Li, Chun; Ma, Sunxiang; Cao, Yi (Frontiers in Bioengineering and Biotechnology, 2021)
Hydrogen sulfide (H2S) has been identified as an important gasotransmitter and biomaterials with H2S-donor capable of sustained-releasing of H2S are considered to be promising in bio-medical applications including would dressing. Endothelial progenitor cells (EPCs) have been proved to enhance would healing. In this paper, nanofibrous membrane was used as carrier of H2S donor and EPCs to promote wound healing. The rMaSp/NaHS nanofibrous membrane electro-spun from recombinant spider silk protein rMaSp blended with hydrogen sulfide (H2S) donor NaHS showed hemocompatibility and cytocompatibility as well as sustained-releasing of H2S. Loaded with endothelial progenitor cells (EPCs), rMaSp/NaHS/EPCs membrane was used as a wound dressing toward a cutaneous wound model in vivo. It was found that rMaSp/NaHS/EPCs membrane could significantly enhance the wound regeneration compared to rMaSp membrane and rMaSp/NaHS membrane. This novel wound dressing will have a broad application prospect in the field of skin tissue regeneration.